Bukti Penghakiman Allah Yang Adil di dalam 2 Tesalonika 1:3-10 Menurut Pendekatan Analisis Wacana - Limasaputra, Alexander Darmawan (Veritas : Jurnal Teologi dan Pelayanan, 2020)
Evidence of God's Righteous Judgment in 2 Thessalonians 1:3-10 According to Discourse Analysis Approach. The theme of the righteous judgment of God is an important theme in 2 Thessalonians 1. This theme has a connection with the situation of the Thessalonians, who were currently undergoing persecution. This paper will explain how Paul developed the theme of God's righteous judgment in 2 Thessalonians 1:3-10 by using the discourse analysis approach. This paper will demonstrate that a righteous God will judge everyone by punishing the oppressors and rewarding the believers. Discourse analysis is used in this paper because it is an approach that can provide a stronger foundation when analyzing a text and provides objective criteria when investigating the problem of a text. The purpose of this paper is to encourage believers to have comfort and strength when experiencing persecution because a righteous God will judge every human being.